High-Resolution Computed Tomography of Nonfibrotic Interstitial Lung Disease - Marrocchio, Cristina; Lynch, David A. (Seminars in Respiratory and Critical Care Medicine, 2022)
Nonfibrotic interstitial lung diseases include a heterogeneous group of conditions that can result in various patterns of lung involvement. When approaching the computed tomographic (CT) scan of a patient with a suspected or known interstitial lung disease, the use of the appropriate radiological terms and a systematic, structured approach to the interpretation of the imaging findings are essential to reach a confident diagnosis or to limit the list of differentials to few possibilities. The large number of conditions that cause nonfibrotic interstitial lung diseases prevents a thorough discussion of all these entities. Therefore, this article will focus on the most common chronic lung diseases that can cause these CT findings. A pattern-based approach is used, with a discussion of nodular pattern, consolidation, crazy paving, ground-glass opacities, septal thickening, and calcifications. The different clinical conditions will be described based on their predominant pattern, with particular attention to findings that can help in the differential diagnosis.
Keywords: CT; interstitial lung diseases; sarcoidosis; pulmonary eosinophilia; aspiration; pneumonia; pulmonary alveolar proteinosis